Catullus 107: a Callimachean reading - D'angour, AJ (Cambridge University Press, 2009)
Extract: ‘Excitement struggles with the restraint of form and language and the artifice of verbal repetition… runs riot.’ The repetition is more pronounced and personal here than in another Lesbia epigram, no. 70, where ‘the repetition dicit…dicit makes it certain that Catullus had [Callimachus, Ep. 25 Pf.] in mind’. Poem 70 illustrates how Catullus might allude to and adapt a Hellenistic model in expressing his personal feelings; while the longer elegiac poems in particular (and 66, the translation of Coma Berenices) show the depth of his engagement with Callimachean literary technique. We should not be surprised to find Callimachean elements here too, given the demonstrable correspondences with poem 68 in particular, a composition noted for its use of Alexandrian artifice. But while there are close echoes of the high emotion, the doctus poeta of 68 seems to be largely missing from 107. Here Catullus exults ipsa refers te / nobis (5–6); there his mistress se nostrum contulit in gremium (132).